Identification of blade operational mode shapes during wear of abradable coating. (28th April 2020) - Tang, N.; Zhang, B.; Lord, C.; Marshall, M.
Abstract: Abradable liner materials are often used in turbine engines between the compressor blade tips and the casing. The abradable liner serves as a partially sacrificial material to improve the overall engine efficiency by creating a tight seal, minimising gas flow leakage. During operation, the rubbing interaction between the blade tips and abradable lined casing induces vibrations in the blades. These vibrations not only can have a significant influence on the wear mechanism and wear efficiency of the blade tips, but also the early fatigue failure of the blades, and therefore are of interest. In this paper, a newly developed approach is presented that can be used to identify the operational blade vibration modes. A non-contact single point laser sensor is used to measure the vibrational displacements during the wear process. A mathematical transform is introduced to correct for blade position due to its rotating frame of reference. After applying the transform, the vibrational energy is calculated at various positions throughout the blade. The continuous wavelet-based modal identification is then introduced to identify the blade mode shape. The Modal Assurance Criterion (MAC) is used to demonstrate the similarity of the mode shapes as a function of wear time illustrating that the blade mode shapes change slightly with the level of wear.